Práticas de leitura do gênero diário pessoal : multiletramentos - Santos, Gisele Fernandes (2020)
This work presents a proposal for multi-course practices that enables a reflective, dynamic, interactive and collaborative teaching and learning process for the formation of autonomous and critical readers at school and in the world that goes beyond its walls. It is based on the assumption that reading is a socio-historically situated literacy event and its literate practices provide multiple reading interactions in the different spheres of human activities. In this context, this paper aims to describe the reading practices of the book “Diary of a Banana: the memories of Greg Heffley” (2008), by Jeff Kinney, with the purpose of instructing readers of the 8th grade of a public school Lagarto / SE to better understand the daily textual genre. It is a proposal that addresses reading and writing activities in a more interactive way, situated in the social and cultural context of the participants, for the construction of a proficient and critical reader and writer. The theoretical assumptions are based on Kalantzis and Cope (2006, 2008) Rojo (2012) and Dionísio (2010) on the pedagogy of multi-tools and multimodal texts; in Marcuschi (2007, 2008) and Machado (1998) regarding textual genres and the daily genre and in Solé (1998) and Kleiman (1998, 2016) about reading and reading and writing strategies. The results show that the reading practices of the personal daily genre proved to be a significant practice for the development of the reading competence of adolescent students, through the insertion of multimodal elements and technologies, aimed at reading and the written production of texts. At the end, a didactic sequence was presented that contains the following steps: presentation and motivation, six modules involving reading and writing strategies of the personal diary and, finally, final digital production and presentation, using the Canva design tool.